#48 A novel UPLC method development, validation and forced degradation studies on Lamivudine and Dolutegravir in combined pharmaceutical dosage form - Dhanabalan, Kamalakannan; Subramaniam, AnandaThangadurai; Ramanathan, Sambathkumar (Journal of Pharmaceutical Chemistry, 2022)
To develop a simple, accurate, precise, and economical method for the simultaneous estimation of the Lamivudine and Dolutegravir in pharmaceutical dosage form by ultra-performance liquid chromatography (UPLC) using tunable ultraviolet (TUV) detector. The separation was achieved on an HSS C18 column (2.6 mm X 50 mm, 1.6 µm,) at a wavelength of 260 nm, using a mobile phase disodium hydrogen phosphate and acetonitrile (70:30 v/v) in an isocratic elution mode at a flow rate of 0.3 mL/min. The retention time for Lamivudine and Dolutegravir was found to be 1.408 min and 1.739 min, respectively. The percentage RSD of the Lamivudine and Dolutegravir was and found to be 0.8 and 0.8 respectively and the percentage recovery was obtained at 100.39% and 100.37%. The LOD, LOQ values were obtained from regression equations of Lamivudine and Dolutegravir were 0.41 ppm, 1.25 ppm, and 0.09 ppm, 0.26 ppm respectively. The regression equation of Lamivudine is y = 24270x + 12218 and Dolutegravir is y = 34783x + 1060. The developed method was found to be simple, accurate, precise, and cost-effective. The forced degradation studies indicated that the degradants and excipients are within the limit. Hence, the developed method was suitable for quantitative analysis of Lamivudine and Dolutegravir both in bulk and combined pharmaceutical dosage form.
Keywords: aaa